THE ROLE OF EMOTIONAL INTELLIGENCE ON WORK-LIFE BALANCE OF NORTH SUMATERA REGIONAL POLICE CRIMINAL OFFICE PERSONNEL WITH SERVING CULTURE AS A MEDIATION - Ananda, Rizky; Hasanuddin, Hasanuddin; Hardjo, Suryani (International Journal of Cultural and Social Science, 2025)
The focus of this research examines the factors that influence work-life balance among police officers; a good work-life balance for police officers can have a positive impact on their job performance.Police can provide good service to the community.Meanwhile, a low work-life balance can negatively impact both mental and physical health.Work-life balance is the balance between roles and responsibilities in both work and outside of work (household and social life).This research uses a quantitative method with a sample size of 279 people.The sampling technique used in this study is purposive sampling.The data collection methods used are the emotional intelligence scale, the work-life balance scale, and the serving culture scale.This research uses the data analysis technique known as Structural Equation Model (SEM).The results of this study indicate that there is an influence of emotional intelligence on Work Life Balance among Polri Personnel, with Serving Culture as a mediator.The results were obtained through testing using the Sobel Test technique, where based on the two-tailed probability value of 0.012 < 0.05, and/or with the Sobel test statistic value of 2.488 > 1.96.